Synthesis of bridged mixed valence macrocyclic metal compounds - Hanack, Michael; Hirsch, Andreas (Synthetic Metals, 1989)
The bridged mixed valence phthalocyaninato dimer pyPcFeCNPcFeNH (1) and the trimer pyPcCoCNPcFeNCPcCopy (2) have been synthesized by coupling reactions of the monomers PcFe (py) CN (3) and PcCo (py) CN (4) containing the central metals in the oxidation state of +III with PcFe (NH) (5) having iron in the oxidation state of +II. These molecules have been characterized by FTIR- and Möβbauer spectroscopy as well as thermogravimetric methods. © 1989.